Persepsi Guru terhadap Penerapan KTSP dan Kurikulum 2013 dalam Mata Pelajaran Bahasa Indonesia - Khair, Ummul; Prasetiana, Dana (ESTETIK : Jurnal Bahasa Indonesia, 2019)
Abstract: This study is motivated by curriculum changes from KTSP to 2013 Curriculum giving different assumptions for each teacher who implements them because there are many differences in the KTSP and Curriculum from the two curricula, starting from the planning, implementation, understanding and response of students. and its assessment. The purpose of this study is to find a clear picture of: 1) teacher perceptions of the application of KTSP in Indonesian language subjects, 2) teacher perceptions of the application of 2013 curriculum in Indonesian language subjects, 3) differences in the application of 2013 KTSP and Curriculum in Indonesian subjects , 4) the most effective curriculum used.This research is a field research which describes / explains word by word descriptively using a qualitative approach. The informants in this study were grade IV teachers. The data source used is primary data by conducting interviews with class IV teachers; and secondary data sources obtained from the internet or books. Data are analyzed by: data collection, data reduction, data presentation, and conclusion drawing.The results showed that teachers' perceptions of the application of KTSP and Curriculum 2013 in Indonesian subjects differed between class IV A teachers and class IV B teachers both in terms of planning, implementation, understanding and response of students and their assessments such as planning using methods that different in the implementation of Indonesian language subjects, Indonesian language learning taught separately in KTSP and using themes in Curriculum 2013, KTSP assessment which focuses on the cognitive realm makes children's understanding of knowledge higher, while the 2013 Curriculum assessment which focuses on the realm affective which emphasizes the character of children in school. The differences in the application of KTSP and Curriculum 2013 in Indonesian language subjects found based on the results of the interviews are outlined in the form of Table.4.5. There are differences in teachers' perceptions of the most effective curriculum used in accordance with the learning experiences of each grade IV teacher if the teacher uses a fun curriculum in the learning process and can increase the potential of students, the curriculum is the most effective to use. Keywords: Perception, KTSP, Curriculum 2013, Indonesian Lang